ID-Based Public Auditing Protocol for Cloud Data Integrity Checking with Privacy-Preserving and Effective Aggregation Verification. (1st November 2018) - Kang, Baoyuan; Si, Lin; Jiang, Hong; Li, Chunqing; Xie, Mingming
Abstract : With the rapid development of cloud service, people with limited storage space can store their data files to the cloud and delete the file in their memory. However, the cloud service provider may change or partly delete user's file for his benefit. Therefore, it is necessary for the user to periodically check the data file integrity. Public auditing protocols are just designated for checking the data file integrity by an auditor on behalf of the user. Recently, based on ID-based cryptography many ID-based public auditing protocols for cloud data integrity checking are proposed. However, some existing protocols are subjected to forgery attack. Other existing protocols cannot preserve the privacy of the user, as the auditor can obtain user's file content through times of auditing the same file blocks. In this paper, we propose a new ID-based public auditing protocol for cloud data integrity checking with optimized structure, privacy-preserving, and effective aggregation verification. We also prove that the proposed protocol can resist forgery attack under the assumption that the Diffie-Hellman problem is hard. Furthermore, we compare our protocol with other ID-based auditing protocols.